Enhancing Commercial Competencies: Key Strategies and Tools - Atanes Torres, Roberto; Lorenzo Ros, Sara; González Rico, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The aim of this study is to examine the potential relationship between soft skills and professional performance, as well as to conduct a thorough statistical analysis of the main soft skills of workers in the commercial sector. The sample consists of 1654 participants from this sector. The results indicate that the sample can be categorised into four distinct homogeneous profiles of professional performance, and that the main soft skills analysed are interrelated and have a direct impact on professional performance. Finally, the results are interpreted with a focus on the realities of the business market.